Analysis Kerusakan Pompa Suplai Bahan Bakar Pada Engine Komatsu Menggunakan Fishbone Analysis - Wilarso Wilarso; Bayu Idianto; Asep Dharmanto (Proceedings Series on Physical & Formal Sciences, 2021)
Leaking fuel from the fuel supply pump will have an impact on decreasing engine reliability. To determine the root cause of the damage, an analysis must be carried out so that the same incident does not happen again. The research method used, visual inspection, collection of maintenance data and using fishbone analysis. The results of the research on the fuel leak from the fuel supply pump contained particles that caused damage to the Seal O Ring. Contamination of the fuel supply pump is due to the quality of the rebuild. To evaluate the recondition process carried out by vendors and internal companies. Then educate every human resource who often makes repairs or overhauls to improve the quality of component reconditioning.